2018
DOI: 10.1089/tmj.2017.0253
|View full text |Cite
|
Sign up to set email alerts
|

Teledermatology in the United States: An Update in a Dynamic Era

Abstract: U.S. teledermatology programs have increased in number and annual consultation volume. Academia is the most prevalent practice setting, and self-pay is the dominant accepted payment method. Innovative platforms and the provision of direct-to-patient care are changing the practice of teledermatology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 69 publications
(49 citation statements)
references
References 31 publications
1
48
0
Order By: Relevance
“…The dissemination and implementation of teledermatology have grown slowly over the past few decades McKoy et al, 2016;Whited, 2015;Yim et al, 2018). With improvement in imaging and communications technology, the diagnostic accuracy of teledermatology has improved steadily.…”
Section: Discussionmentioning
confidence: 99%
“…The dissemination and implementation of teledermatology have grown slowly over the past few decades McKoy et al, 2016;Whited, 2015;Yim et al, 2018). With improvement in imaging and communications technology, the diagnostic accuracy of teledermatology has improved steadily.…”
Section: Discussionmentioning
confidence: 99%
“…SAF uses asynchronous communication meaning the referrer and the provider do not need to be present at the same time. SAF is the most commonly practised modality of teledermatology in the United States and Spain . SAF has been used effectively for a large range of skin conditions and contexts.…”
Section: Teledermatology Practicementioning
confidence: 99%
“…Globally, there are several established successful TD programmes in the USA, the Netherlands and Spain, which have been well documented . However, there is a paucity of published literature on TD systems from the UK.…”
Section: Introductionmentioning
confidence: 99%
“…In the Netherlands, TD has been fully integrated into and reimbursed by the national healthcare system since 2006 . In the USA, there are multiple large‐scale TD programmes, which are mostly reimbursed by private providers, and a recent survey showed that there are 40 active nongovernmental TD programmes in the USA, with a median annual consultation volume comparable to 263 consultations . The Spanish TD network was established in 2004 in Andalusia for skin cancer referrals, and has led to validated improvements in waiting times and rapid reliable screening for skin cancer .…”
Section: Introductionmentioning
confidence: 99%